الحمرة: وبائيات و دور العلاج باللينكومايسين - بدور, رولا (Latakia University Journal -Medical Sciences Series, 2013)
The aim of this research is to study statistically erysipelas cases and its precipitating factors and also to determine the possibility of considering intramuscular injection of lincomycin as an effective treatment of uncomplicated erysipelas instead of intravenous penicillin G. 60 cases of erysipelas were studied and evaluated. There was no significant relation to age, sex and site of infection. The most affected sites were lower limbs, then face, and upper limbs. The most important risk factors were fungal intertrigo, vascular impairment and finally diabetes mellitus. The response to lincomycin treatment was excellent in 71.71%, intermediate in 23.91% of patients, while there was no response in only 4.34% of cases. يهدف البحث إلى إجراء دراسة إحصائية عن الحمرة والعوامل المؤهبة لحدوثها وكذلك جدوى اعتماد اللينكومايسين حقنا عضليا، علاجاً فعالاً بديلاً من العلاج الوريدي بالبنسلين في حالات الحمرة غير المختلطة. تمت دراسة وتقييم 60 حالة حمرة. لم نجد رابطا هاما بين الجنس والعمر أو مكان الإصابة.الموقع الأكثر إصابة كان الساق والأقل الوجه واليد. عامل الخطورة الأهم كان المذح الفطري يليه الاضطراب الوعائي ثم الرض الموضعي و بعده السكري. أما الاستجابة للعلاج باللينكومايسين فكانت ممتازة لدى71.73% من الحالات و متوسطة لدى 23.91% فيما لم تحصل استجابة لدى 4.34% فقط.